Stereochemical investigations on 2-arylimino-3-aryl-thiazolidine-4-one derivatives - Erol, Şule. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
In this study, stereostructures of 2-arylimino-3-aryl-thiazolidine-4-ones have beeninvestigated. The compounds to be studied have been synthesized by the reaction of thecorresponding N,N'-diarylthioureas with -bromoacetic acid. In these compounds the N3-aryl bond rotation is hindered and except for 2-phenylimino-3-phenyl-thiazolidine-4-one the restricted rotation around this bond gives riseto M and P stereoisomers. Therefore, the protons on C-5 of the heterocyclic ring arediastereotopic and give AB type splitting in the 1H NMR spectrum. In addition, as far as C=N double bond is concerned, this bond may have E and Z configurations.In this project, 1H NMR spectra of the compounds were examined in various solventsand the spectra were found to show a strong solvent dependence. For 2-phenylimino-3-phenyl-thiazolidine-4-one and 2-(o-tolyl)imino-3-(o-tolyl)-thiazolidine-4-one both E and Z isomers were found to be present in aromatic solvents revealed by the splittings of thesignals for the protons present at C-5 of the heterocyclic ring. For the other compoundsstudied, 2-(a-naphthyl)imino-3-(a-naphthyl)-thiazolidine-4-one, 2-(o-chlorophenyl)imino-3-(o-chlorophenyl)-thiazolidine-4-one, 2-(o-methoxyphenyl)imino-3-(o-methoxyphenyl)-thiazolidine-4-one and in the other solvents studied, DMF-d7, methanol-d4 and CDCl3, onlyone isomer was observed which was assigned to the Z isomer by comparison of the energybarriers determined with the barriers of the previously studied structurally relatedcompounds. The 2D-NOESY experiments which were used in order to prove the presenceof the E isomer did not show any crosspeaks due to through speace interactions.1H NMR spectra of the compounds taken at various temperatures in order to find outwhether the E and Z isomers were thermally interconvertible, did not show any coalesenceup to 100oC.The stereoisomers were separated using enantioselective HPLC and barriers torotation about N3-aryl bond of the compounds have been determined by thermal racemization of the resolved enantiomers.
Keywords: Stereochemistry.